MANAJEMEN PEMBELAJARAN KETERAMPILAN BAGI ANAK TUNAGRAHITA DI SLBN 1 KOTA BENGKULU - Wenny Irmavera (Manajer Pendididikan, 2022)
This study aims to describe learning management for mentally retarded children, in terms of planning, implementation, evaluation and skills learning barriers for mentally retarded children at SLB Negeri 1 Bengkulu City. This research method is descriptive qualitative. The subjects of this study were the principal, skills coordinator, and skills teacher. Data collection techniques are carried out by observation, interviews, and documentation, where data will be analyzed by collecting, reducing, presenting data, and drawing conclusions. The results showed that the management of learning skills at SLBN 1 Bengkulu City was running as it should, namely by planning to determine learning programs through annual coordination meetings, student assessment tests, and preparation of lesson plans, preparing learning needs related to facilities and infrastructure using BOS budget funds and committees , the implementation of learning is carried out in accordance with the plan using the direct instruction method with teachers who support each skill learning, evaluation is carried out by giving students the opportunity to do internships at institutions outside the school that have partnered and also evaluates the skills learning programs that have been implemented. However, there are still obstacles, namely communication difficulties with students, teacher human resources whose educational background is not relevant, and school infrastructure, as well as rejection from partners where mentally retarded children carry out internships.